Draft Annual Plan 1995-96 Government of Tamil Nadu - Planning Commission (Planning Commission, 1995)
The Annual Plan for 1995-96 assumes significance as it has been drafted after undertaking the Mid-Term Appraisal of the progress of the first three years of the Eighth Five Year Plan. The Eighth Five Year Plan of Tamil Nadu has been formulated within the framework of the National Plan. Eighth Five year Plan for the State envisages an outlay of Rs. 10,200 Crore at 1991-92 prices and aims at a GDP growth rate of 5.6% per annum during the plan period. Our aim has been to ensure that the Plan investment in real terms is stepped up so as to maintain the tempo of development. In the first year of the plan i.e.. 1992-93 the expenditure was Rs. 1935 crore against the approved outlay of Rs. 1766 crore. In 1993-94 as well the plan achievement as per the preliminary actual is Rs.2234.45 crore against the approved outlay of Rs.2102 crore
State Planning Commission
State Planning Commission